Aquation Is a Crucial Activation Step for Anticancer Action of Ruthenium(II) Polypyridyl Complexes to Trigger Cancer Cell Apoptosis. Issue 2 (18th November 2015) - Li, Meng; Lai, Lanhai; Zhao, Zhennan; Chen, Tianfeng
Abstract: Aquation has been proposed as crucial chemical action step for ruthenium (Ru) complexes, but its effects on the action mechanisms remain elusive. Herein, we have demonstrated the aquation process of a potent Ru polypyridyl complex (RuBmp=[Ru II (bmbp)(phen)Cl]ClO4, bmbp=2, 6‐bis(6‐methylbenzimidazol‐2‐yl) pyridine, phen=phenanthroline) with a chloride ligand, and revealed that aquation of RuBmp effectively enhanced its hydrophilicity and cellular uptake, thus significantly increasing its anticancer efficacy. The aquation products (H‐RuBmp=[Ru II (bmbp)(phen)Cl]ClO4, [Ru II (bmbp)(phen)(H2 O)]ClO4, bmbp) exhibited a much higher apoptosis‐inducing ability than the intact complex, with involvement of caspase activation, mitochondria dysfunction, and interaction with cell membrane death receptors. H‐RuBmp demonstrated a higher interaction potency with the cell membrane and induced higher levels of ROS overproduction in cancer cells to regulate the AKT, MAPK, and p53 signaling pathways. Taken together, this study could provide useful information for fine‐tuning the rational design of next‐generation metal medicines. Abstract : Ru a true aquarius ? This study demonstrates that aquation is a crucial activation step for anticancer action of ruthenium(II) polypyridyl complexes to trigger cancer cell apoptosis. The results could provide useful information for fine‐tuning the rational design of next‐generation metal medicines.